Wage Effects of Overeducation Evidence from Poland - Broniatowska, Paulina (Central European Journal of Economic Modelling and Econometrics, 2020)
The educational expansion in many advanced economies in the past few decades has triggered a debate on overeducation. The aim of the study is to provide an empirical evaluation of the wage effects of overeducation in different occupational groups. We also analyse whether these effects differ between genders. In order to achieve this, we use individual data from the Structure of Wages and Salaries by Occupations database of firms with 10 or more employees in Poland. We use data from the 2006-2014 waves of the survey. We calculate the impact of overeducation on wages using a Mincer-type wage regression model. We show that on average workers are rewarded for being overeducated, but the size of wage effects of overeducation differs among particular occupational groups. We show also that the choice of the method of measurement of overeducation affects the results.